CUTANEOUS ADVERSE DRUG REACTIONS IN GENERAL PRACTICE - AN ANALYSIS - G Rajaram,; Sugirda, P.; Lenin, R. (International Journal of Ayurveda and Pharma Research, 2016)
Aim: To study the pattern of cutaneous adverse drug reactions presenting to general practitioners in a semi urban area.  Methodology and Results: This study was conducted among general practitioners of Villupuram, a semi urban area in Tamilnadu State. During the study, a total of 60 CADRs were reported. Data were collected using standard CDSCO ADR form. The majority of CADRs were observed in the age group of 20-40 years. According to WHO causality assessment, 48 were probable and 12 were possible. The severity assessment using modified hartwig and seigel revealed 18 mild, 41 moderate and one severe CADRs. The common drug groups implicated are antibiotics followed by NSAIDS and anticonvulsants. Maculopapular rash was the most common presentation of CADRs.Conclusion: Among the various types of CADRs seen in this study, Maculopapular rash was the most common followed by fixed drug eruption. studies antimicrobials were the most common causative agent followed by NSAIDs and anti- convulsants. This study on CADRs gains importance as the pattern of drug use is changing periodically and everyday many new drugs enter the market.